Identification of novel and conserved miRNAs involved in pollen development in Brassica campestris ssp. chinensis by high-throughput sequencing and degradome analysis - Jiang, Jianxia (BioMed Central, 2014)
BACKGROUND: microRNAs (miRNAs) are endogenous, noncoding, small RNAs that have essential regulatory functions in plant growth, development, and stress response processes. However, limited information is available about their functions in sexual reproduction of flowering plants. Pollen development is an important process in the life cycle of a flowering plant and is a major factor that affects the yield and quality of crop seeds. RESULTS: This study aims to identify miRNAs involved in pollen development. Two independent small RNA libraries were constructed from the flower buds of the male sterile line (Bcajh97-01A) and male fertile line (Bcajh97-01B) of Brassica campestris ssp. chinensis. The libraries were subjected to high-throughput sequencing by using the Illumina Solexa system. Eight novel miRNAs on the other arm of known pre-miRNAs, 54 new conserved miRNAs, and 8 novel miRNA members were identified. Twenty-five pairs of novel miRNA/miRNA* were found. Among all the identified miRNAs, 18 differentially expressed miRNAs with over two-fold change between flower buds of male sterile line (Bcajh97-01A) and male fertile line (Bcajh97-01B) were identified. qRT-PCR analysis revealed that most of the differentially expressed miRNAs were preferentially expressed in flower buds of the male fertile line (Bcajh97-01B). Degradome analysis showed that a total of 15 genes were predicted to be the targets of seven miRNAs. CONCLUSIONS: Our findings provide an overview of potential miRNAs involved in pollen development and interactions between miRNAs and their corresponding targets, which may provide important clues on the function of miRNAs in pollen development.